Signal-anchor sequences are an essential factor for the Golgi-plasma membrane localization of type II membrane proteins. Issue 10 (3rd October 2018) - Kikegawa, Tatsuki; Yamaguchi, Takuya; Nambu, Ryohei; Etchuya, Kenji; Ikeda, Masami; Mukai, Yuri
ABSTRACT: Despite studies of the mechanism underlying the intracellular localization of membrane proteins, the specific mechanisms by which each membrane protein localizes to the endoplasmic reticulum, Golgi apparatus, and plasma membrane in the secretory pathway are unclear. In this study, a discriminant analysis of endoplasmic reticulum, Golgi apparatus and plasma membrane-localized type II membrane proteins was performed using a position-specific scoring matrix derived from the amino acid propensity of the sequences around signal-anchors. The possibility that the sequence around the signal-anchor is a factor for identifying each localization group was evaluated. The discrimination accuracy between the Golgi apparatus and plasma membrane-localized type II membrane proteins was as high as 90%, indicating that, in addition to other factors, the sequence around signal-anchor is an essential component of the selection mechanism for the Golgi and plasma membrane localization. These results may improve the use of membrane proteins for drug delivery and therapeutic applications. Graphical abstract: : The sequence around the signal-anchor is an essential component of the selection mechanism for Golgi and plasma membrane protein localization.